Ultrasonographically detected renal fusion anomalies in Western Region of Nepal - Shrestha, OK; Shrestha, GL (Journal of Chitwan Medical College, 2014)
To establish the incidence and patterns of renal fusion anomalies based on Ultrasonography (USG) in Western region of Nepal. In 2 years period, patients undergoing abdominal USG at Gandaki Medical College between 2010 and 2012 were screened for renal fusion anomalies. After identification, incidence and male:female ratio were stratified for total renal fusion anomalies, horseshoe kidney, crossed fused ectopia and fused pelvic kidney. Out of 31498 patients who underwent abdominal USG, there were 71(1:444) cases of renal fusion anomalies, 61 (1:516) of horseshoe kidneys, 9 (1:3500) of crossed-fused ectopia and 1 (1:31498) of fused pelvic kidney. Male:Female ratio was 1:2 for horseshoe kidney and 1.25:1 for crossed fused ectopia. Renal fusion anomalies are rare congenital malformation. USG is a sensitive and reliable modality for its detection. Horseshoe kidney is the most common renal fusion anomaly followed by crossed fused ectopia. Our ultrasonograhic evaluation for incidence of renal fusion anomalies closely matches past autopsy and radiographic data. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10857 Journal of Chitwan Medical College 2014; 4(2): 25-28